PENGEMBANGAN MODUL BERNUANSA ISLAMI DALAM PEMBELAJARAN MATEMATIKA PADA MATERI STATISTIKA UNTUK PESERTA DIDIK SMA KELAS XI IPA - Usmadi Usmadi; Iftitahurrahmah Iftitahurrahmah; Ergusni Ergusni (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2022)
This study aims to produce teaching materials in the form of Islamic-nuanced mathematics learning modules. The Islamic nuanced module is a teaching material that combines mathematics with religious knowledge. This research is a research development (Research Development). The research method is using four D (4-D). This model consists of 4 stages but in this study only 3 stages were carried out, namely defining, designing and developing. The type of data used is qualitative data obtained from teacher interviews and observation sheets regarding the practicality of the module. Quantitative data were obtained from the results of module validation, and students' practical response questionnaires. The module developed was tested at SMAN 2 Padangpanjang. The results of the validity test of the Islamic nuanced mathematics learning module by the validator obtained a value of 72.3% with valid criteria and the practicality results obtained a value of 87.13% with practical criteria. Practical values are obtained from observations by observers, questionnaire responses by students and interview sheets by mathematics teachers. Based on the results of the study, it can be concluded that the Islamic nuanced module in mathematics learning in statistics material for high school students in class XI science is valid and practical.